The Impact of Perceived Physician Communication Skills on Revisit Intention: A Moderated Mediation Model - NWOSU, Laurine; YESILADA, Figen; AGHAEI, Iman; AHMED, Japheth (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2025)
This study aims to evaluate the impact of perceived physician communication skills on patients’ revisit intention, focusing on the mediating role of two dimensions of trust and the moderating role of gender. While several studies on revisit intention examine the effect of service quality as a whole, this is one of the few that not only focuses solely on physician-patient communication but also examines both dimensions of trust and revisit intention with the same physician. A cross-sectional survey was employed via questionnaire distribution. A total of 265 valid responses were used for data analysis. The findings revealed that perceived physician communication skills impact trust and revisit intention. Emotional trust was seen to have a full mediating effect on the relationship. Gender had no moderating effect on the proposed relationship, which suggests that irrespective of gender, patients’ expectations and preferences for effective communication are similar. By cultivating a supportive and empathetic attitude, physicians can create a positive emotional environment that enhances patient trust and positive behavioral intentions